Laryngeal malignancy: relation of tumor size and neck node metastasis - Koirala, K; Sharma, V (Nepal Journal of Medical Sciences, 2013)
Background: Laryngeal malignancy is a common pathological entity. Size of the primary tumor and neck node metastasis both are bad prognostic features. Purpose of this retrospective study is to see if the tumor size of primary laryngeal squamous cell carcinoma correlates with the neck node metastasis. Methods: Patients of all ages and both sex with biopsy proven squamous cell carcinoma of larynx were included in the study. After detailed history taking and clinical examination to identify the size of the primary tumor and neck node metastasis, biopsy was taken from the primary site under general anesthesia. Fine Needle Aspiration Cytology (FNAC) of the palpable neck node(s) was also performed. Data were analyzed using SPSS software for windows. Results: Fifty seven new cases of laryngeal squamous cell carcinoma with mean age of 72.71 were included in the study. Supra glottic layrnx was the most common site affected. Neck node metastasis was more frequent in tumor of bigger size (higher T stage) and the difference was statistically significant (p=0.001). Conclusion: The size of primary laryngeal squamous cell carcinoma correlates with the neck node metastasis. This information can be used for the therapeutic implementation as well. Nepal Journal of Medical Sciences | Volume 02 | Number 01 | Jan-Jun 2013 | Page 48-51 DOI: http://dx.doi.org/10.3126/njms.v2i1.7652